Molecular detection of sugarcane striate virus and sugarcane white streak virus and their prevalence in the Miami World Collection of sugarcane and related grasses. (22nd May 2020) - Boukari, Wardatou; Filloux, Denis; Daugrois, Jean Heinrich; Fernandez, Emmanuel; Mollov, Dimitre; Kaye, Claudia; Hincapie, Martha; Sanchez, Alexander; Wang, Jianping; Roumagnac, Philippe; Rott, Philippe
Abstract: Viruses in the genus Mastrevirus (family Geminiviridae ), including those infecting sugarcane, have natural geographical ranges almost exclusively restricted to Africa and the Indian Ocean islands off the African coast. Only sugarcane white streak virus (SWSV) in Barbados and sugarcane striate virus (SStrV) in Florida and Guadeloupe are known to infect a few sugarcane varieties in the Western Hemisphere. In this study, PCR assays were developed to detect these two viruses in sugarcane. Five hundred and seventy‐one DNA samples from Saccharum species and interspecific hybrids from the Miami World Collection of sugarcane and related grasses were tested for the presence of SStrV and SWSV by PCR. No variety was found infected by SWSV but SStrV was detected in 19 varieties. PCR data were confirmed by sequencing amplified fragments (248 bp). These fragments shared 93%–100% nucleotide identity with SStrV sequences from the GenBank database. SStrV isolates were distributed in six phylogenetic groups, including the four strains of the virus. Most varieties infected by SStrV originated from Asia, thus confirming a previous hypothesis stating that this virus originated from this continent. Absence of SStrV in commercial sugarcane in Florida also suggested that this virus has not been spread in this location, while infected plants have been present for several decades. Abstract : Sugarcane striate virus (SStrV) but not sugarcane white streak virus (SWSV) was detected by PCR in a world collection of Saccharum species in Florida where SStrV was confined to imported varieties.